A sequential one-pot approach to 1, 2, 4, 5-tetrasubstituted-2H-imidazole synthesis from disubstituted alkynes1. (24th September 2015) - Boominathan, Siva Senthil Kumar; Chen, Chung-Yu; Huang, Po-Jui; Hou, Ruei-Jhih; Wang, Jeh-Jeng
<x xml:space="preserve">Abstract</x> A sequential one-pot method was developed to prepare 2H-imidazole scaffolds from internal alkynes and various ketones with good substrate scope and high yields.